PENDIDIKAN MULTIKULTURALISME DALAM ISLAM - suluri suluri (Religi: Jurnal Studi Agama-agama, 2019)
Indonesia is one of the largest multicultural countries in the world. It is not uncommon for us to hear social conflicts, whether related to ethnicity, race, culture or religion. Islam is a religion that carries the mission of Rohmatan lil'aalamiin, a religion that carries a mission of peace, compassion, both for others and the entire universe. then Multiculturalism Education multiculturalism education is an obligatory thing to be studied, understood and implemented in Indonesia, especially for Islamic education institutions. Islamic education which has the concept of Rahmatan Lil Aalamiin should be an example in addressing differences in multicultural societies. Thus, the output produced by educational institutions is not only competent with the disciplines they are engaged in, but also able to apply the values of rahmatan lil'aalamiin in understanding and appreciating in multicultural society.